Religion and Depression in Adolescence - Fruehwirth, Jane Cooley; Iyer, Sriya; Zhang, Anwen (Journal of Political Economy, 2019)
Depression is the leading cause of illness and disability in adolescence. Many studies show a correlation between religiosity and mental health, yet the question remains whether the relationship is causal. We exploit within-school variation in adolescents' peers to deal with selection into religiosity. We find robust effects of religiosity on depression that are stronger for the most depressed. These effects are not driven by the school social context; depression spreads among close friends rather than through broader peer groups that affect religiosity. Exploration of mechanisms suggests that religiosity buffers against stressors in ways that school activities and friendships do not.